2018
DOI: 10.1029/2018ja025457
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale F Region Neutral Winds Associated With Quasi‐steady and Transient Nightside Auroral Forms

Abstract: High‐latitude neutral winds often circulate in a two‐cell pattern as driven by large‐scale auroral forcing. However, auroral forcing also occurs in various types of mesoscale forms (i.e., tens to hundreds of kilometers in space and a few to tens of minutes in time) and contains more energy input over mesoscale than large scale. A question arises as to whether and how winds respond to the mesoscale forcing. We characterize F region winds associated with various types of auroral forms using scanning Doppler imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 46 publications
8
31
0
Order By: Relevance
“…In addition to the wind responses to different substorm phases, we inferred that strong meridional gradient of the zonal wind on a spatial scale of tens of kilometers may exist in the vicinity of the growth‐phase moving arc, as shown in E3. The small‐scale wind structures have been identified using scanning Doppler imagers (e.g., Anderson et al, ; Conde et al, ; Dhadly & Conde, ; Kosch et al, ; Zou et al, ). Conde et al () found a meridional wind shear associated with an auroral arc in the dusk sector moving with the arc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the wind responses to different substorm phases, we inferred that strong meridional gradient of the zonal wind on a spatial scale of tens of kilometers may exist in the vicinity of the growth‐phase moving arc, as shown in E3. The small‐scale wind structures have been identified using scanning Doppler imagers (e.g., Anderson et al, ; Conde et al, ; Dhadly & Conde, ; Kosch et al, ; Zou et al, ). Conde et al () found a meridional wind shear associated with an auroral arc in the dusk sector moving with the arc.…”
Section: Discussionmentioning
confidence: 99%
“…This is understood to be due to the increased ionization brought about from particle precipitation, increasing ion-neutral collision frequencies, and thus coupling. Similar observations were also made by Zou et al (2018). Both of these studies exploited results from a Scanning Doppler Imager (SDI), a type of FPI which can measure more than one single point neutral wind measurement (Conde & Smith, 1997), setting it apart from traditional FPIs.…”
Section: Introductionmentioning
confidence: 63%
“…As studied by Conde et al (2018) and Zou et al (2018), the drastic increase in ion density introduced by precipitation will enhance the neutral-ion collision frequency, which in turn strengthens ion drag. However, the potential variability of lags with local time, and thus universal time, is not well understood and could affect the results shown here.…”
Section: 1029/2019ja026627mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the Cluster observations indicate that patches are associated with Region 1 sense FAC structures and a downward Poynting flux, this work contradicts the notion that the source of the lobe features associated with patches are generated in the ionosphere. The results of this study are therefore important for our understanding of mesoscale magnetospheric forcing on open magnetic field lines and ion-neutral coupling within patches (such as that discussed in Zou et al, 2018).…”
Section: Discussionmentioning
confidence: 95%